Combined Surface Micropatterning and Reactive Chemistry Maximizes Tissue Adhesion with Minimal Inflammation. Issue 4 (18th September 2013) - Pereira, Maria J. N.; Sundback, Cathryn A.; Lang, Nora; Cho, Woo Kyung; Pomerantseva, Irina; Ouyang, Ben; Tao, Sarah L.; McHugh, Kevin; Mwizerwa, Olive; Vemula, Praveen K.; Mochel, Mark C.; Carter, David J.; et al.
<x xml:space="preserve">Abstract</x> The use of tissue adhesives for internal clinical applications is limited due to a lack of materials that balance strong adhesion with biocompatibility. The use of substrate topography is explored to reduce the volume of a highly reactive and toxic glue without compromising adhesive strength. Micro‐textured patches coated with a thin layer of cyanoacrylate glue achieve similar adhesion levels to patches employing large amounts of adhesive, and is superior to the level of adhesion achieved when a thin coating is applied to a non‐textured patch. In vivo studies demonstrate reduced tissue inflammation and necrosis for patterned patches with a thinly coated layer of reactive glue, thus overcoming a significant challenge with existing tissue adhesives such as cyanoacrylate. Closure of surgical stomach and colon defects in a rat model is achieved without abdominal adhesions. Harnessing the synergy between surface topography and reactive chemistry enables controlled tissue adhesion with an improved biocompatibility profile without requiring changes in the chemical composition of reactive tissue glues.